Figma Masuk Sekolah: Inovasi Pembelajaran UI Design untuk Generasi Digital - Karina Auliasari; Mira Orisa; Mariza Kertaningtyas; Zulkifli Abdillah; Muhammad Rafi Faddilani; Fathur Riski; Jamil Nashrulloh; Bagaskara Adhi P (Pusat Riset dan Inovasi Nasional, 2025)
UI design training using the FIGMA platform implemented at SMKN 2 Singosari is a community service activity carried out by a team of lecturers and students of Informatics Engineering S1 and Industrial Engineering S1 at ITN Malang. Students of the RPL expertise program class XI SMKN 2 Singosari have gained an understanding and expertise in UI design from the results of the training activities. The mastery and understanding of the training material by students is shown from the questionnaire score, which averages 5 on a scale of 5 for understanding the material and a value of 4.2 for teaching satisfaction during the training. As many as 80% of students also expressed their satisfaction with the quality of the teaching team in delivering the material and their patience in overseeing the UI design practice material. The results shown show that the FIGMA community service program entering schools has succeeded in supporting innovative learning that supports the skills of the current digital generation in the vocational high school education environment.